Peran Wali Kelas Dalam Pengelolaan Anak Berkebutuhan Khusus di SDN 1 Banda Aceh - T. M. Haekal (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2020)
The child with special needed need special assistance from the school side, the homeroom teacher is no exception. At Banda Aceh 1 Elementary School, children with special needs are managed in accordance with applicable standards. This study aims to determine the role, strategies and obstacles of homerooms in the management of children with special needs at SDN 1 Banda Aceh. This research is a qualitative research with data collection techniques, namely: observation, interviews, and documentation. The analysis was carried out by miles and huberman techniques. Research results include: 1). The role of homeroom is that it is very much needed even very important in terms of the management of children with special needs. As the right of the homeroom teacher in managing his students in the classroom, his roles include making plans for implementing learning, designing syllabi, media, and modifying curriculum. 2). Homerooms in the management of special needs children are homeroom teachers and special mentoring teachers always accompany regular students and children with special needs during the learning process until the learning is complete, the classroom atmosphere is always made fun sometimes there are also students who are bored so the teacher becomes more active in looking after. The homeroom teacher understands that management is not only theoretically using his own instincts. Obstacles are the lack of skills in exploring children with special needs because education personnel are not graduates of schools for children with special needs. Management of children with special needs carried out by teachers at SDN 1 Banda Aceh, management can be done well, as evidenced by students always playing an active role in learning and students are able to carry out evaluations conducted by the teacher. And for the next researcher, hopefully it can study more deeply about the management of homeroom teachers and special teachers in managing and handling children with special needs (ABK) and the factors that influence barriers to better complement and refine this research.